Análise dos polimorfismos do KISS1 em meninas com puberdade precoce central - Goncalves, Eline Maria Stafuzza [UNIFESP] (2013)
BACKGROUND: Puberty may be influenced by genetic, nutritional, environmental and socioeconomic factors. However, its etiology is unknown. The influence of the kisspeptin-GPR54 complex in the hypothalamus-pituitary-ovarian axis is known, but not its exact mechanism. This research may help in the diagnosis and to find better treatment to patients with central precocious puberty, and, consequently reduce the problems resulting from this early ripening. OBJECTIVES: To evaluate the association between the polymorphisms of the gene KISS1 and central precocious puberty. METHODS: 184 patients from the Gynecology of Childhood and Adolescence Ambulatory, from the Department of Gynecology, UNIFESP-EPM, were divided into: Control Group - made up of 107 girls without central precocious puberty and Case Group - composed of 77 girls diagnosed with central precocious puberty. Eight polymorphisms were analyzed, related to exon 2 and 3 of the gene KISS1 by using DNA extracted from peripheral blood collected. RESULTS: The polymorphisms E and F of exon 3, previous described, weren?t found. There was no association between the polymorphisms of KISS1 and central precocious puberty. There was significant difference between caucasian and non-caucasian ethnic groups in relation to polymorphism of exon 2 and G of exon 3, hypothesizing be protective factors. CONCLUSION: Although we did not find relation between polymorphisms KISS1 and precocious puberty, this process has multiple mechanisms and perhaps interaction with environmental factors may be decisive for the early process.